(untitled) (Aporte Santiaguino, 2023)
The research was developed in the district of Huaraz, the objective was to determine values of ballast coefficients in the 05 geotechnical zones established in the seismic microzonation plan of the town and then use them in mathematical models that consider the soil-structure interaction, for this The methodology that was followed was through an applied type of research, with a correlational level, a non-experimental - transversal design, having the 05 geotechnical zones as the population and sample. To search for the data, the appropriately distributed load plate test and special laboratory tests were carried out. The results obtained from the load plate test were grouped into 03 zones, Zone I has a ballast coefficient variation between 0.50 to 2.00 kg/cm3, zone II between 2.01 to 4.00 kg/cm3 and zone III between 4.01 to 7.00 kg/cm3, the research concludes with the modeling of a house considering soil-structure interaction, where an inversely proportional relationship was found between the values of ballast coefficients with the mezzanine distortion of the house, zone I presented greater mezzanine distortion by having unfavorable values, while zone III reflected lower distortion values by having higher values of ballast coefficients.